IN-HOSPITAL BLOOD PRESSURE VARIABILITY AS A PREDICTOR OF CARDIOVASCULAR EVENTS AND RENAL DYSFUNCTION IN THE SETTING OF ACUTE MYOCARDIAL INFARCTION. (April 2021) - Mantzouranis, M.; Tsioufis, K.; Konstantinou, K.; Kolokathis, K.; Koumelli, A.; Kalos, T.; Kouremeti, M.; Yfantis, A.; Magkas, N.; Fragoulis, C.; Kasiakogias, A.; Leontsinis, I.; et al.
Abstract: Objective: Recent data have associated blood pressure variability (BPV) with cardiovascular morbidity and renal dysfunction but not in the setting of acute coronary syndrome (ACS). The aim of this study is to determine the impact short-term BPV on in-hospital cardiovascular outcomes and renal function in patients suffering a myocardial infarction (MI). Design and method: A total population of 250 MI patients (79.6% male; mean age 62.5 years;68.4% hypertensives)underwent 24-h ambulatory BP measurement during their hospitalization. The parameters of BPV analyzed were: a) 24-h standard deviation (SD), b) coefficient of variation (CV) and c) average real variability (ARV) of systolic and diastolic BP. The study population was divided intoa STEMI (n = 127) and a non-STEMI (n = 123) group. Cardiovascular outcomes included: new onset of ACS, pulmonary edema, hypertensive emergency, life threatening arrhythmias, whereas worsening of renal function (WRF) was defined as a reduction of GFR > or = 25% according to the RIFLE criteria. No deaths or strokes occurred. Results: In the total population a significant association was demonstrated between SBP CV andthe incidence of cardiovascular outcomes (OR = 1.136; 95% CI: 0.452–1.819; P = 0.001). After separate analysis for each MI group, SBP CV remained a predictor in the STEMI group (OR = 1.825; 95% CI: 0.814–2.835; P = 0.001). Regarding WRF CV SBP demonstrated a prognostic role (OR = 1.946; 95% CI:0.923–2.969; P < 0.001)in the entire population. Results for STEMI group were similar (OR = 3.769; 95% CI:2.056–5.481; P < 0.001). However, non-STEMI group failed to demonstrate any significant associations. We therefore, conducted multivariate regression models for STEMI group, in which the CV SBP retained predictive value of cardiovascular outcomes (OR = 1.502; 95% CI:0.470–2.534; P = 0.005) and WRF (OR = 4.139; 95% CI:2.423–5.962; P < 0.001)independently of age, gender, history of hypertension, diabetes mellitus (DM), smoking and low-density lipoprotein (LDL-C). Conclusions: In the setting of STEMI, assessment of BPV using CV could have a prognostic role of in-hospital cardio-renal outcomes suggesting a clinical need for further individualization of BP regulation in the integrative ACS management.